Synthesis of Organic–Inorganic Lead Halide Perovskite Nanoplatelets: Towards High‐Performance Perovskite Solar Cells and Optoelectronic Devices. Issue 9 (23rd May 2014) - Ha, Son Tung; Liu, Xinfeng; Zhang, Qing; Giovanni, David; Sum, Tze Chien; Xiong, Qihua
<x xml:space="preserve">Abstract</x> Highly crystalline organic–inorganic lead halide perovskite nanoplatelets are grown on muscovite mica utilizing van der Waals epitaxial growth followed by thermally intercalating methyl ammonium halides. The resulting CH3NH3PbI3 platelets show excellent optical properties with an electron diffusion length of more than 200 nm, which is approximately two times higher than that of the solution‐processed film, suggesting considerable promise in photovoltaics and optoelectronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>